Immediate postplacental insertion of intrauterine contraceptive device (copper 375) and its complications in term of expulsion, infection and perforatio - Khanzada, Benish; Shahani, Mala Jitendra; Khanzada, Areesha Kamran (Clinical Journal of Obstetrics and Gynecology, 2018)
Objective: To determine the complications (infection, perforation and expulsion rate) of immediate postplacental insertion of intrauterine contraceptive device (Multiload Copper375) in postnatal patients. Methods: A case series study was conducted between October 28, 2014 to April 30, 2018 in obstetrics and gynaecology department, Civil Hospital Karachi,-+ Informed consent was taken. Intrauterine contraceptive device (Multiload) was inserted immediately within 10 min after delivery of placenta. These women were observed to determine outcome (infection, perforation and expulsion) at the time of discharge and 6 weeks postpartum. Absence of all these were taken as satisfactory outcome. Results: A total of 435 women were included in this study. 165 (38%) were delivered through cesarean section and 270 (62%) were delivered through vaginally. There were 36 (8.3%) cases of infection. The cumulative rate of expulsion and perforation at the end of sixth week of post insertion was 39 (9%) and 0% respectively and 360 (82.8%) had satisfactory outcome. Post-placental placements during cesarean delivery are associated with lower expulsion rates than post-placental vaginal insertions without increasing rates of postoperative complications like perforation, slightly increase infection rate following vaginal delivery. Conclusions: Immediate postpartum insertion of IUCD is an effective, safe and easily reversible method of contraception. Rates of the complications (Infection, expulsion and perforation) are remarkably low.